Disease Progression and Obstetric Outcomes of Women with Multiple Sclerosis at a Reference Center in Northeastern Brazil - Gabrielle Maria Carvalho de Barros; Bianca Etelvina Santos de Oliveira; Gabriela Januário Oliveira; Rômulo Kunrath Pinto Silva; Thiago Nóbrega Cardoso; Sabina Bastos Maia (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To describe the obstetric outcomes of patients withmultiple sclerosis (MS) and the impact of pregnancy and the postpartum period on the progression of the disease. Methods A case series study performed between December 2019 and February 2020, reporting pregnancies occurred between 1996 and 2019. The subjects included were women with MS undergoing follow-up at an MS referral center in Northeastern Brazil, and who had at least one pregnancy after the onset of MS symptoms, or who had their first relapse in the first year after delivery. Results In total, 26 women and 38 pregnancies were analyzed - 32 of them resulted in delivery, and the remaining 6, in miscarriages. There was a significant increase in the prevalence of relapse during the postpartum period when compared with the gestational period. In 16 (42.1%) of the pregnancies, there was exposure to diseasemodifying therapies (DMTs) - 14 (36.8%), to interferon β, and 2 (5.3%), to fingolimod. Higher rates of abortion, prematurity and low birth weight were reported in the group was exposed to DMT when compared with the one who was not. Conclusion In the sample of the present study, there was a significant increase in the rate of MS relapse during the postpartum period when compared with the gestational period. Additionally, it seems that exposure to DMTs during pregnancy may affect the obstetric outcomes of the patients.